2015
DOI: 10.1021/acs.energyfuels.5b01152
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Tar Derived from Principle Components of Municipal Solid Waste

Abstract: It is of great interest and importance to have a comprehensive understanding of the characteristics of tar derived from major components of municipal solid waste to guide gasification syngas cleaning and upgrading. In this paper, cellulose and polyvinyl chloride (PVC) were chosen as principle components, and the surface tension, kinematic viscosity, and contact angle of tar derived from cellulose, PVC, and their mixture at temperatures of 400, 500, and 600 °C were experimentally studied. Gas chromatography−mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Pyrolysis oils derived from waste materials are important sources of fuel and chemicals that both circumvent some of the environmental concerns associated with petroleum and alleviate waste disposal concerns. A wide range of organic waste materials, such as forestry residue and recycled plastics, may be used for pyrolysis, each producing a complex oil product with attributes governed by their chemical composition. As for other complex mixtures, such as petroleum and dissolved organic matter, pyrolysis oils contain thousands of distinct molecular formulas. , Fractionation simplifies these samples, allowing for more detailed chemical characterization, which provides a better understanding of bulk properties and potential applications. Previous pyrolysis oil fractionation methods have focused on the separation of oxygenated species from biomass pyrolysis oils, whereas analysis of municipal waste pyrolysis oils has largely been conducted without separation.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis oils derived from waste materials are important sources of fuel and chemicals that both circumvent some of the environmental concerns associated with petroleum and alleviate waste disposal concerns. A wide range of organic waste materials, such as forestry residue and recycled plastics, may be used for pyrolysis, each producing a complex oil product with attributes governed by their chemical composition. As for other complex mixtures, such as petroleum and dissolved organic matter, pyrolysis oils contain thousands of distinct molecular formulas. , Fractionation simplifies these samples, allowing for more detailed chemical characterization, which provides a better understanding of bulk properties and potential applications. Previous pyrolysis oil fractionation methods have focused on the separation of oxygenated species from biomass pyrolysis oils, whereas analysis of municipal waste pyrolysis oils has largely been conducted without separation.…”
Section: Introductionmentioning
confidence: 99%
“…As of 2013, only ∼35% of municipal solid waste generated in the U.S. was recycled, leaving ∼170 million tons of waste to be disposed of by other methods . Pyrolysis has proven useful for the conversion of biomass and waste materials into fuel sources, and the chemical composition of biomass-derived pyrolysis oils has been studied extensively by gas chromatography (GC), mass spectrometry (MS), Fourier transform infrared spectroscopy (FT-IR), elemental analysis, nuclear magnetic resonance (NMR), and various extraction methods. Pyrolysis of municipal solid wastes offers a unique opportunity to reduce costly and environmentally harmful waste storage practices and to generate alternative fuel streams.…”
Section: Introductionmentioning
confidence: 99%
“…The high content of heteroatoms in pyrolysis oils, especially oxygen, is the greatest hindrance to their use as a substitute for crude oil. The chemical composition of pyrolysis oil is greatly influenced by the feedstock . Pyrolysis oils derived from plant biomass typically contain between 10 and 30 wt % oxygen due to the cellulosic/lignin-based (high oxygen content) starting material. ,,, Islam et al showed that the oxygen content of paper waste-derived pyrolysis oils can be as high as 53 wt % .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations